Traditional Authority of Kyai and Its Impact on Religious Moderation in East Java Pesantren - Al-Ghifari, Devano Hilmy; Huda, Mokhammad Miftakhul; Haider, Aftab (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
The traditional authority of kyai in pesantren significantly influences religious moderation in East Java, making it a crucial issue to study amidst growing social harmony and diversity challenges. Previous studies have predominantly focused on the educational and spiritual aspects of pesantren without delving deeply into the role of kyai in shaping values of moderation. This research aims to analyze how the traditional authority of kyai in pesantren influences the practice of religious moderation, particularly in the context of East Java’s local culture. A descriptive qualitative method with a case study approach was employed. The research focused on pesantren in East Java, known for their strong influence in local communities. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis involved reduction, data presentation, and conclusion drawing. The findings reveal that kyai play a central role as social mediators, integrating local culture to foster harmony. The novelty of this research lies in showing how tradition and local wisdom can be adapted to reinforce religious moderation in the context of globalization.